2014
DOI: 10.5012/bkcs.2014.35.6.1675
|View full text |Cite
|
Sign up to set email alerts
|

Peroxopolyoxotungsten-based Ionic Hybrid as a Highly Efficient Recyclable Catalyst for Epoxidation of Vegetable oil with H2O2

Abstract: A peroxopolyoxotungsten-based ionic hybrid was synthesized by anion-change of peroxopolyoxometalate (POM) PW 4 O 24 3− with dicationic long-chain alkyl imidazolium ionic liquids. The characterization was conducted by FT-IR, TGA, 1 H-NMR and CHN Elemental analyses. Its catalytic performance was evaluated by the epoxidation of soybean oil with H 2 O 2 under solvent-free condition, including testing of organic cations influence, catalytic reusability and reaction conditions. The catalyst was proved to be a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Since then, it has drawn wide attention in the following three decades [12][13][14][15] as effective catalysts for the epoxidation of double bond. Recently, Zhang et al [16] and Wu et al [17] utilized PHA as the catalyst in the soybean oil epoxidation, which confirmed its high catalytic activity and recyclable efficient.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since then, it has drawn wide attention in the following three decades [12][13][14][15] as effective catalysts for the epoxidation of double bond. Recently, Zhang et al [16] and Wu et al [17] utilized PHA as the catalyst in the soybean oil epoxidation, which confirmed its high catalytic activity and recyclable efficient.…”
Section: Introductionmentioning
confidence: 93%
“…Since then, it has drawn wide attention in the following three decades as effective catalysts for the epoxidation of double bond. Recently, Zhang et al and Wu et al utilized PHA as the catalyst in the soybean oil epoxidation, which confirmed its high catalytic activity and recyclable efficient. Gao et al reported that PHA reacted with H 2 O 2 to form soluble small molecules species, shuttling the active oxygen from water phase to oil phase, and then the oxirane group was formed in the organic phase.…”
Section: Introductionmentioning
confidence: 95%
“…In the literature, the PPOM catalyst structure is usually used for the selective epoxidation of vegetable oils and their derivatives. 42,147 It was found that the epoxidation of soybean oil provides an epoxide yield of more than 90% during 3-4 h at 60 C under mild conditions. 147 However, it was investigated that the active sites of the catalysts are lost in the course of the reaction and, consequently, deactivation of the catalysts, decrease in activity and selectivity occur.…”
Section: The Use Of Polyoxometalatesmentioning
confidence: 99%
“…The reaction takes place preferentially in the organic phase via the active oxygen atom and oxirane group was formed in the organic phase. [42][43][44][45] Chemoenzymatic epoxidation commonly using Novozyme 435 has become an alternative means for the epoxidation of oils as an environmentally friendly process. 6,[46][47][48] Other heterogeneous catalysts such as HY zeolite, 49 SiO 2 @ (CH 2 ) 2 COOOH, 50 sulfated-SnO 2 , 51 Nb-SiO 2 , 52 CoCuAl layered double hydroxides, 53 commercial alumina, [54][55][56] copper supported on alumina with cumene and O 2 as the oxidant, 57 poly(4-vinylpyridine)CH 3 ReO 3 supported on halloysite nanotubes, 58 Ti-incorporated mesoporous silica, 59 and N 2 O 5 -SiO 2 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…These recycling results are in accordance with previous studies by other groups using similar homogeneous polyoxotungsten-based epoxidation catalysts, who also described a significant drop in activity after successive epoxidation runs. 42,43 Efficient recycling has been achieved using polyoxotungsten-based catalysts immobilised on graphene and polymer supports, 44,45 however, these heterogeneous systems generally require longer reaction times and higher temperatures for epoxidation to occur. Finally, we found that the catalyst distillate residue isolated after the fourth run was highly flammable, which affords the opportunity of burning it for energy and recovering its tungsten metal content (Fig.…”
Section: Catalyst Recycling Studiesmentioning
confidence: 99%